2021
DOI: 10.3934/mbe.2021368
|View full text |Cite
|
Sign up to set email alerts
|

A novel dynamic brain network in arousal for brain states and emotion analysis

Abstract: <abstract> <sec><title>Background</title><p>Brain network can be well used in emotion analysis to analyze the brain state of subjects. A novel dynamic brain network in arousal is proposed to analyze brain states and emotion with Electroencephalography (EEG) signals.</p> </sec> <sec><title>New Method</title><p>Time factors is integrated to construct a dynamic brain network under high and low arousal conditions. The transfer entropy is adopted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 40 publications
6
6
0
Order By: Relevance
“…This indicates frontal, temporal, and parietal areas of the brain provide more emotion-related information. This is consistent with previous literatures [47] [48] [49]. Emotion arousal is mostly reflected in the frontal lobe, temporal lobe, and parietal lobe [47].…”
Section: Interpretabilitysupporting
confidence: 93%
See 3 more Smart Citations
“…This indicates frontal, temporal, and parietal areas of the brain provide more emotion-related information. This is consistent with previous literatures [47] [48] [49]. Emotion arousal is mostly reflected in the frontal lobe, temporal lobe, and parietal lobe [47].…”
Section: Interpretabilitysupporting
confidence: 93%
“…This is consistent with previous literatures [47] [48] [49]. Emotion arousal is mostly reflected in the frontal lobe, temporal lobe, and parietal lobe [47]. Pre-frontal and temporal asymmetry have close relations to arousal recognition [48].…”
Section: Interpretabilitysupporting
confidence: 93%
See 2 more Smart Citations
“…EEG signals are the overall response of the electrophysiological activity of human brain nerve cells in the cerebral cortex or scalp surface [ 10 ]. Clinical studies have shown that EEG signals contain a lot of physiological and pathological information [ 11 ], and different mental states will affect the changes of EEGs, which provides an important basis for the diagnosis of depression and other brain diseases. Campisi, P. et al [ 12 ] pointed out that the brain regions of patients with depression have changed, which reduces the decision-making ability of patients with depression.…”
Section: Introductionmentioning
confidence: 99%